En memoria del Dr. José Pacheco Romero - Távara Orozco, Luis (2025)
I am grateful to the Peruvian Society of Obstetrics and Gynecology for conferring upon me the great honor of writing this profile, which I am sure will not be easy given the significance of Dr. José Pacheco’s life for Peruvian medical science, as hehas devoted his entire professional career to the advancement of Peruvian obstetrics and gynecology.